DIET THERAPY OF RHEUMATOLOGIC DISEASES USING LOCAL PRODUCTS AND NATIONAL DISHES (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
According to the World Health Organization, rheumatic diseases cause 1/3 of all cases of temporary disability and about 10% of all disabilities.